2012
DOI: 10.1007/s11276-012-0449-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and improvement of CDS-based topology control for wireless sensor networks

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Abstract-The Connected Dominating Set (CDS) principle has emerged as the predominant method for energy-efficient discovery and clustering of power-/location-unaware WSN nodes. While many CDS discovery protocols have been proposed recently, a one-to-one comparative evaluation of these protocols has not been performed on judicious metrics. In this paper, we perform a simulation-based evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Literatures [16][17][18][19] have addressed redundant coverage problem. Khedr et al [16] have proposed an algorithm to find minimum connected sensor cover based on largest coverage, highest residual energy and minimum communication cost.…”
Section: Cds For Redundant Coveragementioning
confidence: 99%
See 1 more Smart Citation
“…Literatures [16][17][18][19] have addressed redundant coverage problem. Khedr et al [16] have proposed an algorithm to find minimum connected sensor cover based on largest coverage, highest residual energy and minimum communication cost.…”
Section: Cds For Redundant Coveragementioning
confidence: 99%
“…Each backbone node has backup nodes for promoting the energy efficiency and fault-tolerant capability of the network. A clique based CDS construction algorithm with reduced message overhead to provide better sensing coverage is proposed by Qureshi et al [18]. They have also proposed an algorithm named ''poly'' based on the idea of polygons and have shown that the formation of polygon in the network provides a reliable and energy efficient topology [19].…”
Section: Cds For Redundant Coveragementioning
confidence: 99%
“…Literatures [8][9][10][11][12][13][14][15] consider energy issue. Wu et al have also proposed two rules based on node degree and node's energy level to construct power aware CDS in [8,9].…”
Section: ) Cds Construction In Ad Hoc Networkmentioning
confidence: 99%
“…Shukla et al [14] have proposed a weighted CDS construction based on energy, degree and ID. Yu et al [15] propose a CDS based topology control algorithm for wireless sensor network. El-Hajj et al [16] have proposed a distributed CDS construction algorithm for routing in MANET.…”
Section: ) Cds Construction In Ad Hoc Networkmentioning
confidence: 99%
“…The metrics of energy efficiency [5] included energy consumption, average energy, standard deviation of energy, throughput, and energy balance, but these metrics were analyzed, respectively. Network size, message overhead, energy overhead, residual energy, and convergence time were also, respectively, used to discuss the energy efficiency of clustering protocols [6]. Darabkh et al investigated how the sensor density affected the performance of clustering algorithms [2].…”
Section: Introductionmentioning
confidence: 99%